MODEL PEMBIAYAAN BAGI HASIL DAN INOVASI BISNIS TERHADAP PERTUMBUHAN PELANGGAN DAN KINERJA USAHA TANI TEBU MIKRO DAN KECIL DI KABUPATEN BONDOWOSO - Mohamad Dimyati; M Fathorrazi; Andriana Andriana (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
The purpose of this study was to determine and analyze the influences of profit sharing financing system to the business innovation, and to perform business, assets to the business innovation, and to perform business innovation to customer growth, and to business performance, customer growth to the performances of business. The type of this research is exploratory research study. The population was Sugarcane Farming’s in Kab.Bondowoso. The amount of Small and Micro Sugarcane Farming’s who use financing funds are 50 units. The sampling technique conducted with a purposive sampling technique. The research showed that Financing have a significant effect on business innovation. Furthermore, profit sharing financing also have a significant effect on the performance of sugar cane farming. The asset of sugar cane farming has an effect on business innovation, and affects the performance of sugar cane farming. Business innovation effect on customer growth, and performance sugar cane farming. Customer growth affects the performance sugar cane farming.